2020
DOI: 10.1007/s11292-020-09441-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and social distancing measures in Queensland, Australia, are associated with short-term decreases in recorded violent crime

Abstract: Objectives The objective of this study is to test whether recorded rates of violent crime declined in the context of social distancing regulations in Queensland, Australia. Methods ARIMA modeling was used to compute 6-month-ahead forecasts of rates for common assault, serious assault, sexual offenses, and breaches of domestic violence orders. These forecasts (and their 95% confidence intervals) are compared to the observed data for March and April 2020. Results By the end of April, 2020, rates of common, serio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(175 citation statements)
references
References 22 publications
8
166
1
Order By: Relevance
“…Many have noted that most street crimes have decreased during lockdown due to reduced opportunities for physical convergence between offenders and targets (Ashby 2020a;Mohler et al 2020), as has also been shown in the UK (see Figure 1), while domestic abuse may increase since perpetrators and victims are required to remain confined in the same space for long periods of time (Piquero et al 2020). Some argue that the massive move towards home working and online shopping during the outbreak may also contribute to a displacement of crime opportunities from offline to online environments (Collier et al 2020;Hawdon et al 2020;Payne 2020;Payne et al 2020). In other words, as persons spend more time connected to the Internet, and less time on the streets, opportunities for street violent and property crimes decrease while Internet crimes may increase (Miró-Llinares and Moneva 2019).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many have noted that most street crimes have decreased during lockdown due to reduced opportunities for physical convergence between offenders and targets (Ashby 2020a;Mohler et al 2020), as has also been shown in the UK (see Figure 1), while domestic abuse may increase since perpetrators and victims are required to remain confined in the same space for long periods of time (Piquero et al 2020). Some argue that the massive move towards home working and online shopping during the outbreak may also contribute to a displacement of crime opportunities from offline to online environments (Collier et al 2020;Hawdon et al 2020;Payne 2020;Payne et al 2020). In other words, as persons spend more time connected to the Internet, and less time on the streets, opportunities for street violent and property crimes decrease while Internet crimes may increase (Miró-Llinares and Moneva 2019).…”
Section: Introductionmentioning
confidence: 91%
“…Our results suggest that reports of cyber-dependent crime and online fraud have increased during the COVID-19 outbreak, and rates of cybercrimes have been particularly high during months with the strictest lockdown policies. Lockdown measures and social distancing policies imposed by governments worldwide to prevent the spread of the virus have caused unprecedented effects on the way people interact, consume, conduct business, deliver services and find opportunities for crime (Felson et al 2020;Payne et al 2020). The everyday routine activities of millions of individuals have moved from physical to online environments, and opportunities for crime appear to have shifted towards cyber-dependent or cyber-enabled crime.…”
Section: Conclusion and Word Of Cautionmentioning
confidence: 99%
“…In March and April 2020, there were no observed increases in reports of FV to police in New South Wales (Freeman, 2020a(Freeman, , 2020b, nor identified breaches in protection orders in Queensland Payne, Morgan, & Piquero, 2020). However, these findings were derived from a short time-period and official reports.…”
Section: Evidence Pointing Towards An Increase In Fv Since the Covid-mentioning
confidence: 95%
“…Halford et al (2020) used a similar modeling approach to estimate the effect of COVID-19 lockdowns on crime in one UK police area, and found that all crime had declined dramatically by one week after the lockdown. Similarly, Payne et al (2020) used ARIMA forecasting to estimate the effect of lockdowns on crime in Queensland, Australia, and found significant declines assault and sexual assault, though domestic violence patterns were not affected. Campedelli et al (2020) used Bayesian structural time-series models to estimate the effect of social distancing policies on crime in Los Angeles and found significant decreases in overall crime, robbery, shoplifting, theft and battery.…”
Section: Routine Activities Lockdowns and Crimementioning
confidence: 99%
“…The potential effects of pandemic-related lockdowns on crime have generated much academic interest. However, to date little research has been conducted outside of a few select countries that tend to be over-represented in criminological research: the US (Ashby, 2020a(Ashby, , 2020bCampedelli, Aziani, & Favarin, 2020;Mohler et al, 2020;Piquero et al, 2020;Shayegh & Malpede, 2020), Europe (Buil-Gil, Miró-llinares, Moneva, & Díaz-Castaño, 2020;Gerell, Kardell, & Kindgren, 2020;Halford, Dixon, Farrell, Malleson, & Tilley, 2020), and Australia (Payne, Morgan, & Piquero, 2020).…”
Section: Introductionmentioning
confidence: 99%